Takaful Batasan Gharar dalam Asuransi Syariah: Analisis Fiqh Klasik dan Model Takaful Kontemporer - Hari Risky Syahputra; Muhamad Zen (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Gharar is a concept that should be avoided due to the uncertainty inherent in financial transactions according to Islamic law. In conventional insurance practices, the element of gharar is considered quite dominant, especially in terms of uncertainty in a contract. This study aims to analyze the limitations of gharar based on the perspective of classical Islamic jurisprudence and how the principles of the takaful model become a form of contemporary insurance. This study uses a qualitative method with a comparative descriptive analysis approach to classical Islamic jurisprudence literature on takaful practices. The results of this study indicate that gharar fahisy (severe) is strictly prohibited, while gharar light (Yasir) can be tolerated in contracts (tabarru) and with the application of the principles of transparency, fairness, and separation of participant and manager funds. This study concludes that Islamic insurance, through the takaful system, has succeeded in significantly minimizing gharar in accordance with Islamic jurisprudence, thus becoming an ethical and Sharia-compliant financial solution.